2002
DOI: 10.1159/000066581
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Confidence in Dermoscopical Methods for Detection of Malignant Melanoma

Abstract: Background: At present, different methods are available for the detection of malignant melanoma or for monitoring of melanocytic nevi (MN). Diagnostic accuracy and time consumption increase from naked-eye inspection (NEI) to handheld dermoscopy (HHD), digital dermoscopy (DD) including image analysis, and teledermoscopy (TD) supported by a specialist in dermoscopy. Effectiveness in daily routine depends on both physician’s experience and patient’s compliance. Objective: To analyse patient’s confidence in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Interestingly, in a survey assessing confidence in various examination techniques for pigmented lesions, Schiffner et al 25 reported that patients are more confident with dermatoscopy compared with naked-eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a survey assessing confidence in various examination techniques for pigmented lesions, Schiffner et al 25 reported that patients are more confident with dermatoscopy compared with naked-eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…1 need to excise a lesion. [11][12][13][14][15][16][17][18] Recent dermoscopy studies provide new understanding of factors that influence nevus pattern and offer intriguing insights into nevogenesis. Herein, we present a synopsis of the most common dermoscopic patterns associated with nevi and the factors influencing the nevus pattern in a given individual, and we discuss some of the recent concepts of nevogenesis.…”
Section: Editor's Notementioning
confidence: 99%
“…While these results appear promising, another study comparing SDDI to TBP found that SDDI resulted in a significantly higher number of biopsies per patient (1.1 with SDDI versus 0.59 for TBP; p <0.001), possible lower melanoma detection rates (2.2% with SDDI versus 5.5% with TBP; p = 0.088) and longer estimated times for clinic appointments [7]. Two studies examining the use of SDDI in patients without at least one risk factor for melanoma (representing a low-risk population) failed to identify any malignancies despite median follow up durations of 6 and 24 months [30,31]. These results, in conjunction with the high biopsy ratio of 79:1 in the low risk arm of the Haenssle et al, trial; suggest that SDDI is of most utility in the high-risk groups [23].…”
Section: Citation: Hand M Chien a Grossman D (2015) Screening And Nmentioning
confidence: 99%
“…Dermoscopy (also called epiluminescence microscopy) improves biopsy ratios by enhancing the diagnostic confidence of providers, and has been extensively reviewed in the literature [35,36]. Melanoma diagnosis with dermoscopy is subjective and varies with provider experience [30,37,38]. Consequently, Automated Dermoscopic Diagnostic (ADD) programs have been applied to dermoscopy images in an attempt to reduce subjective analysis.…”
Section: Dermoscopymentioning
confidence: 99%